Whole Exome Sequencing Aids the Diagnosis of Fetal Skeletal Dysplasia - Tang, Hui; Zhang, Qin; Xiang, Jingjing; Yin, Linliang; Wang, Jing; Wang, Ting (Frontiers in Genetics, 2021)
Skeletal dysplasia is a complex group of bone and cartilage disorders with strong clinical and genetic heterogeneity. Several types have prenatal phenotypes. And it is difficult to make a molecular diagnosis rapidly.In this study, the genetic cause of 16 Chinese fetuses with skeletal dysplasia were analyzed, and 12 cases yielded positive results including one deletion in DMD gene detected by SNP-array and 14 variants in other 6 genes detected by whole exome sequencing (WES). In addition, somatic mosaicism was observed. Our study expanded the pathogenic variant spectrum and elucidated the utilization of WES in improving the diagnosis yield of skeletal dysplasia.